2023
DOI: 10.1126/sciadv.add2120
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides uniformis and its preferred substrate, α-cyclodextrin, enhance endurance exercise performance in mice and human males

Abstract: Although gut microbiota has been linked to exercise, whether alterations in the abundance of specific bacteria improve exercise performance remains ambiguous. In a cross-sectional study involving 25 male long-distance runners, we found a correlation between Bacteroides uniformis abundance in feces and the 3000-m race time. In addition, we administered flaxseed lignan or α-cyclodextrin as a test tablet to healthy, active males who regularly exercised in a randomized, double-blind, placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…Deconditioning and reconditioning periods affected relative abundance of the Bacteroidetes phylum in this study. A greater abundance of Bacteroidetes has been reported in lean or aerobically trained humans (Morita et al., 2023 ; Motiani et al., 2020 ) and animals (Evans et al., 2014 ). Correspondingly, we observed a decrease and an increase in some of the Bacteroidetes OTUs following deconditioning and reconditioning, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Deconditioning and reconditioning periods affected relative abundance of the Bacteroidetes phylum in this study. A greater abundance of Bacteroidetes has been reported in lean or aerobically trained humans (Morita et al., 2023 ; Motiani et al., 2020 ) and animals (Evans et al., 2014 ). Correspondingly, we observed a decrease and an increase in some of the Bacteroidetes OTUs following deconditioning and reconditioning, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…The most significant discrepancy was noted for Bacteroides uniformis , which drastically decreased in abundance in the low-power group and increased in the high-power group. Bacteroides uniformis facilitates glucose production and enhances physical performance [ 59 ]. Roseburia inulinivorans showed the highest sensitivity with regards to VO 2 max, with a slightly more significant decrease in the low group than in the high group.…”
Section: Resultsmentioning
confidence: 99%
“…35 Additionally, a study of Japanese longdistance runners found an association between Bacteroides uniformis and endurance exercise performance, with α-cyclodextrin supplementation increasing B. uniformis and improving endurance exercise performance. 36 Moreover, Bacteroides plebeius has been reported to inhibit chronic kidney disease-induced muscle atrophy in animal models. 37 These findings may suggest a beneficial association between the Bacteroides genus and sarcopenia and skeletal muscle phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…An aerobic exercise training intervention for older Japanese women increased the relative abundance of Bacteroides and was positively correlated with walking performance 35 . Additionally, a study of Japanese long‐distance runners found an association between Bacteroides uniformis and endurance exercise performance, with α‐cyclodextrin supplementation increasing B. uniformis and improving endurance exercise performance 36 . Moreover, Bacteroides plebeius has been reported to inhibit chronic kidney disease–induced muscle atrophy in animal models 37 .…”
Section: Discussionmentioning
confidence: 99%